The coordinated controller design for dual excitation and steam valve of synchronous generator. (2017) - Zhang, Han; Li, Shengtao; Liu, Xiaomei; Ren, Xiuyan; Wang, Zhenhua
This paper focuses on the coordinated controller design of nonlinear dual excitation and steam valve in a synchronous generator to improve transient stability of power system. Based on immersion and invariance method, the designed nonlinear coordinated controller not only can achieve stability of the power angle and adjustment of frequency and voltage, but also can ensure the transient and asymptotic stability of a closed-loop system. The numerical simulation demonstrates that the designed controller is effective.